E-Business Supply Chain Collaboration Measurement Scale: A Confirmatory Approach - Mohammad Jamil Adaileh; Hamzah Elrehail (International Journal of Supply Chain Management, 2018)
This study focuses on the confirmatory factor analysis for testing validity and reliability of E-Business Supply chain collaboration measurement scale in Arabian context. Items of the Scale was developed initially from literature review in supply chain collaboration. The initial form was pilot tested using The study is considered as the first in the Middle East E- business supply chain environment, especially in the Kingdom of Saudi Arabia, which is witnessing rapid growth in the use of electronic commerce between business partners along supply chain. It provided a valid and reliable measurement tool adapted to the Saudi business environment.